A qualitative exploration of which resident skills parents in pediatric emergency departments can assess. (1st November 2016) - Moreau, Katherine A.; Eady, Kaylee; Frank, Jason R.; Hamstra, Stanley J.; Karwowska, Anna; Murnaghan, Aleisha; Pound, Catherine M.; Tse, Sandy; Jabbour, Mona
Abstract: Background : Residents must strive for excellence in their nontechnical skills (NTS). However, NTS have not traditionally been well-assessed in pediatric emergency departments (EDs). One underutilized assessment strategy is to have parents assess the residents caring for their children. Prior to involving parents in resident assessment, it is essential to identify which NTS parents in pediatric EDs can assess. Aim : To explore which resident NTS parents in pediatric EDs can assess. Methods : An exploratory qualitative study design was used. It included interviews with faculty members involved in the supervision and assessment of residents in a pediatric ED and residents who had experience working in a pediatric ED, as well as focus groups with parents who had visited a pediatric ED at least twice in the past year. Results : Participants in this study suggested that parents, if provided with the opportunity, can assess residents' communication skills, comfort in a pediatric setting, adaptability, and collaboration. Conclusions : This study demystifies how parents can become involved in the assessment of residents' NTS. The findings will inform the development of assessment strategies and could be used to develop assessment instruments that enable parents to become actively involved in the assessment of residents in pediatric EDs.